Trimeric hexa-dimethyltin-functionalized selenotungstate [Sn(CH3)2(CH3COO)3Sn(CH3)23Se2W18O62(OH)(H2O)3]18−. Issue 16 (31st March 2016) - Chen, Wei-Chao; Qin, Chao; Wang, Xin-Long; Wu, Cai-Xia; Li, Yang-Guang; Zang, Hong-Ying; Shao, Kui-Zhan; Su, Zhong-Min; Wang, En-Bo
Abstract : The trimeric hybrid organic–inorganic selenotungstate(iv ) [Sn(CH3 )2 (CH3 COO)3 Sn(CH3 )2 3 Se2 W18 O62 (OH)(H2 O)3 ] 18− involving the first reported carboxyl-modified dimethyltin moieties exhibits photocatalytic H2 evolution activity. Abstract : The trimeric organic–inorganic hybrid selenotungstate(iv ) [Sn(CH3 )2 (CH3 COO)3 Sn(CH3 )2 3 Se2 W18 O62 (OH)(H2 O)3 ] 18− is composed of three Wells–Dawson-type α-Se2 W18 fragments and six (CH3 )2 Sn 2+ groups involving the first reported carboxyl-modified dimethyltin moieties, exhibiting photocatalytic H2 evolution activity.